Penerapan Manajemen Layanan Sirkulasi Dalam Meningkatkan Kepuasan Pengguna Perpustakaan di SMA Negeri 18 Bone - A, Astuti; Misbah, Nurlaelah; Mangenre, Fadli (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2024)
This thesis discusses internal circulation service managementincreasing library user satisfaction at SMA Negeri 18 Bone.This research is researchqualitative (Qualitative Research). The approach used consists of two, namelyManagement and psychology. The data collection technique used isobservation, interviews and documentation. The research results show that 1) Service managementLibrary circulation at SMA Negeri 18 Bone covers several important aspects.The member registration process ensures authorized user identification,facilitate administration, and improve user experience. Borrowing,returns and billing are managed systematically and computerizedto ensure regulatory compliance and service efficiency. Officer claritycirculation services, supported by easily accessible locations, helpusers get help and information quickly; 2) Managementcirculation services in increasing library user satisfaction in high schoolsNegeri 18 Bone is carried out through a simple and transparent procedure,easy to fulfill service requirements, easy member card service processfast, the condition of the library materials is good and complete, and the officers are clear circulation services. Efficient circulation service procedures, easy requirementsfulfilled, the condition of library materials is orderly, and the clarity of the staff helpsin providing a consistent user experience, making it easieraccessibility, and improve compliance with library rules, whichall of which contribute to a positive institutional image and improved qualitylearning at the school.